Singlet fission and tandem solar cells reduce thermal degradation and enhance lifespan. (5th May 2021) - Jiang, Yajie; Nielsen, Michael P.; Baldacchino, Alex J.; Green, Martin A.; McCamey, Dane R.; Tayebjee, Murad J. Y.; Schmidt, Timothy W.; Ekins‐Daukes, Nicholas. J.
Abstract: The economic value of a photovoltaic installation depends upon both its lifespan and power conversion efficiency. Progress toward the latter includes mechanisms to circumvent the Shockley‐Queisser limit, such as tandem designs and multiple exciton generation (MEG). Here we explain how both silicon tandem and MEG‐enhanced silicon cell architectures result in lower cell operating temperatures, increasing the device lifetime compared to standard c‐Si cells. Also demonstrated are further advantages from MEG enhanced silicon cells: (i) the device architecture can completely circumvent the need for current‐matching; and (ii) upon degradation, tetracene, a candidate singlet fission (a form of MEG) material, is transparent to the solar spectrum. The combination of (i) and (ii) mean that the primary silicon device will continue to operate with reasonable efficiency even if the singlet fission layer degrades. The lifespan advantages of singlet fission enhanced silicon cells, from a module perspective, are compared favorably alongside the highly regarded perovskite/silicon tandem and conventional c‐Si modules. Abstract : The operating temperature of PV modules affects the rate of degradation. We show the extent to which module operating temperature can be reduced by increasing the efficiency of the PV module via a tandem architecture or singlet Fission, the latter being of interest as a potentially endothermic process. PV modules that employ tetracene as a singlet fission material are found to be resilient against degradation since the degradation product is transparent to solar radiation.